EFFECT OF ALOE VERA EXTRACT AND DISCHARGE PLANNING TO ACCELERATE WOUND HEALING OF OLDER ADULT HERNIA SURGERY PATIENTS - Mukhammad Toha; Mokh Sujarwadi; Ida Zuhroidah (Nurse and Health: Jurnal Keperawatan, 2019)
Background: Older adult patients who underwent hernia surgery commonly get obstacles in the process of wound healing as a result of decline of body functions. Aloe vera which contains of anti-inflammatory, anti-microbial and skin fibroblasts stimulator, can be used as adjunctive therapy in treating wounds.Objective: This study aimed to identify the effect of aloe vera extract and discharge planning to accelerate wound healing of older adult hernia surgery patients at dr. R. Soedarsono General Hospital, Pasuruan.Method: This study uses Quasi-Experimental with Static-group comparison approach. The population is all post-operative hernia patients aged 55-65 years at the operating room of dr. R. Soedarsono General Hospital, Pasuruan. The sample consists of 20 respondents taken according to the inclusion criteria. The independent variable is the treatment of wounds using aloe vera extract accompanied by discharge planning, while the dependent variable was the acceleration of wound healing especially inflammatory and proliferation phases. The data were collected through observation of macroscopic current wound care. Data were analyzed using nonparametric Mann Whitney test with significance level of < 0.05.Result: The results showed the effect of the treatment using aloe vera extract and discharge planning to accelerate wound healing of older adult hernia surgery patients, the inflammatory phase of healing occurs on the sixth day for inflammation, exudation, and edema (p = 0.022, p = 0.028, and p = 0.029, respectively). The proliferative phase occurs on day three with p = 0.015.Conclusion: This research indicates further research on the benefits of aloe vera and discharge planning for wound healing especially in older adult patients is required. Thus, a stronger basis for recommending aloe vera extract as complementary therapy for wound care is available. Key words: Aloe Vera, Discharge Planning, Surgical Wound, Older Adults Age.